A lasting impression: telemedicine in urogynecology during the coronavirus disease 2019 pandemic. Issue 6 (December 2020) - Serna-Gallegos, Tasha; Ninivaggio, Cara S.
Abstract : Purpose of review: Amidst the worldwide coronavirus disease 2019 pandemic, a new medical landscape revolving around telemedicine has arisen. The purpose of this review is to describe and analyze current urogynecologic guidelines for optimizing usage of telemedicine when treating women with pelvic floor disorders. Recent findings: Women managed by urogynecologists are on average older, and hence more likely to have comorbidities that make them susceptible to developing coronavirus disease 2019 with severe symptoms. Telemedicine is key in minimizing exposure without sacrificing treatments and quality of life. Recent studies published prior to the pandemic helped set the stage for successful components of virtual care. Nonsurgical options are crucial to beginning a treatment plan while elective surgeries are still restricted in many hospitals. Medication management and innovative technology, such as smart telephone applications, play a prominent role. The comprehensive literature review discussed here describes the degree of evidence supporting each management option, while also noting the limitations of telemedicine. Summary: Telemedicine has opened a new door for the field of urogynecology allowing for continued safe, evidence-based care. The pandemic culture has tipped the balance away from surgery and toward nonsurgical treatments while attempting not to sacrifice outcomes or quality of care.